The Ability of Primary Teachers to Create HOTS-Based Mathematics Questions in The Certain Teachers PPG Program at Universitas Muhammadiyah Cirebon - Putik Rustika; Sati Sati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Nowadays, in the era of the Merdeka curriculum, there is a strong demand to foster high-order thinking skills (HOTS). However, many teachers struggle to create mathematics questions based on Higher-Order Thinking Skills, especially in mathematics study. When teachers are accustomed to creating contextual mathematical problems and high-level thinking, this can also influence the development of students’ abilities in high-level mathematical thinking, especially in improving critical thinking skills. he PPG (Professional Teacher Education) Certain Teacher program at Universitas Muhammadiyah Cirebon (UMC) is one of the government programs designed to improve the quality of teachers who will receive educator certification. Certain teachers is a term for teachers who teach and are registered in Dapodik, qualifying them to obtain an educator certification. This research aims to investigate the ability of certain elementary school teachers in the PPG Certain Teacher Program to create HOTS-based mathematics questions and to identify the supporting and inhibiting factors in creating the questions. This research uses qualitative research methods with a case study approach, using observations, and interviews. Meanwhile, the research procedures include preparation, interviews, observations, documentaions and data processing. The subjects of the research are three teachers in the PPG certain teacher UMC. The result of this research can be summarized in four sections as follows:  teachers’ ability to design questions based on the cognitive domain of bloom’s taxonomy, teachers’ ability to create questions that promote critical thinking skills, teachers’ ability to find information sources in creating non-routine questions, and the challenges they face in creating HOTS-based mathematics questions.